Type I IFN autoantibodies underlie chikungunya live-attenuated vaccine encephalitis - Adrian Gervais; Paul Bastard; Qian Zhang; Marie-Christine Jaffar-Bandjee; Lucy Bizien; Lotfi Dahmane; Marie-Pierre Moiton; Julien Jabot; Radj Cally; Alexis Maillard; Etienne Frumence; Xavier de Lamballerie; et al. (Proceedings of the National Academy of Sciences, 2026)
Human autoantibodies neutralizing type I interferons (IFNs) have emerged as strong, common, and global determinants of a growing number of severe viral diseases, including hypoxemic viral pneumonia, arboviral encephalitis, and adverse reaction to the live-attenuated yellow fever virus (YFV) vaccine. Chikungunya virus (CHIKV) is a growing global health concern that the live-attenuated vaccine VLA1553 (IXCHIQ®) was developed to address. In 2025, five unrelated adults (aged 82 to 88) on the island of La Réunion (France) developed severe reactions postvaccination; two died. The three patients with encephalitis (aged 84 to 85), including one lethal case, had immunoglobulin G autoantibodies in the blood neutralizing high concentrations of both IFN-α and -ω on admission. An 82-y-old survived rhabdomyolysis without encephalitis, and an 88-y-old died during hospitalization following CHIKV infection despite late vaccination; both lacked autoantibodies against type I IFNs. Autoantibodies neutralizing type I IFNs underlie all three cases of live-attenuated CHIKV vaccine encephalitis studied. Individuals with autoantibodies neutralizing type I IFNs should not be inoculated with live-attenuated YFV and CHIKV vaccines.